Pelatihan Kerajinan Eceng Gondok di Kecamatan Banyubiru untuk Menumbuhkan Wirausaha Baru - Ning Setiati; Amin Retnoningsih; Nur Kusuma Dewi (Journal of Dedicators Community, 2020)
The aim of community service carried out by KKN students in Kebondowo Village and Demakan Village, Banyubiru District, located around Rawapening, is 1) to provide easy use of water hyacinth; 2) provide practical skills in the use of social media for marketing; 3) reduce the skill level of the skill briefing. The methods used in completing the objectives are 1) training in material assistance, 2) practical assistance to finishing, 3) business analysis and marketing. The results of these mentoring activities are: 1) increased workforce capable of making handicrafts from water hyacinth in a number of forms; 2) product marketing at the Rawa Pening lake attraction, Bukit Cinta and provincial level bazaar and expo events; also 3) helps businesses make social media also join in and fill content with product images. Overall, the outputs from this service were obtained and strived to be owned, strived to be independent, production, and consultation with UNNES.